Exploring the relationship between nature sounds, connectedness to nature, mood and willingness to buy sustainable food: A retail field experiment - Spendrup, Sara; Hunter, Erik; Isgren, Ellinor (Appetite, 2016)
Nature sounds are increasingly used by some food retailers to enhance in-store ambiance and potentially even influence sustainable food choices. An in-store, 2 × 3 between-subject full factorial experiment conducted on 627 customers over 12 days tested whether nature sound directly and indirectly influenced willingness to buy (WTB) sustainable foods. The results show that nature sounds positively and directly influence WTB organic foods in groups of customers (men) that have relatively low initial intentions to buy. Indirectly, we did not find support for the effect of nature sound on influencing mood or connectedness to nature (CtN). However, we show that information on the product's sustainability characteristics moderates the relationship between CtN and WTB in certain groups. Namely, when CtN is high, sustainability information positively moderated WTB both organic and climate friendly foods in men. Conversely, when CtN was low, men expressed lower WTB organic and climate friendly foods than identical, albeit conventionally labelled products. Consequently, our study concludes that nature sounds might be an effective, yet subtle in-store tool to use on groups of consumers who might otherwise respond negatively to more overt forms of sustainable food information.